Cultural Racism–Related Stress in Black Caribbean Immigrants: Examining the Predictive Roles of Length of Residence and Racial Identity. (October 2014) - Case, Andrew D.; Hunter, Carla D.
Scholars maintain that with greater length of residence, the U.S. context adversely affects Black immigrants (e.g., via racism-related stress). Yet, the psychological mechanisms that account for increases in racism-related stress over time are unclear. Racial identity scholarship provides reason to suspect Black immigrants' racial identities may partially explain these increases. In this study, Black Americans and Black Caribbean immigrants ( N = 171) responded to measures of cultural racism–related stress and the "identity" (importance of racial group membership to the self-concept) component of racial identity. We expected identity importance to (a) positively predict cultural racism–related stress for both populations and (b) mediate the association between length of residence and cultural racism–related stress in Black Caribbean immigrants. Although no significant mean difference in identity importance existed between groups, identity predicted cultural racism–related stress only in Black Americans. In Black Caribbean immigrants, identity was not a mediator, but length of residence positively predicted cultural racism–related stress. Differences in results across the two populations may indicate important distinctions in racial identity function between Black Caribbean immigrants and Black Americans.